Evaluation of Clinical and Immunological Characteristics of Children with Common Variable Immunodeficiency - Gülsüm Alkan; Sevgi Keles; İsmail Reisli (Hindawi Limited, 2018)
Background. Common variable immunodeficiency (CVID) is a primary immunodeficiency disorder (PID) that typically presents with hypogammaglobulinemia and impaired antibody production. Objectives. This study aimed to promote the awareness of CVID, whose clinical spectrum is quite broad. Methods. The demographic, clinical, and laboratory characteristics of 12 children (seven males and five females) with CVID were analyzed retrospectively. The patients were diagnosed using the diagnostic criteria of the European Society for Primary Immunodeficiencies. Results. The median disease onset age was 7.2±4.1 years, and the mean diagnosis age was 11.6±3.7 years. The diagnosis delay was 4.3±2.6 years, and the parental consanguinity rate was 75%. Most patients presented with recurrent infections, including upper respiratory tract infections (n=8), lower respiratory tract infections (n=9), and gastroenteritis (n=5). In addition, growth retardation (n=9) and bronchiectasis (n=5) were common comorbidities. Two patients presented with autoimmune thrombocytopenia and anemia, and one patient exhibited lung empyema. All the patients had immunoglobulin G deficiencies. Conclusion. CVID is a heterogeneous disease, so the diagnosis is frequently delayed. In the CVID patients with pulmonary complications, relationships were seen with the diagnosis delay, symptom onset age, and lung infection prevalence. Overall, the early diagnosis and treatment of PIDs can preclude life-threatening complications.